Chronic Pulmonary Diseases and COVID-19 - Çakır Edis, Ebru (Turk Thorac J, 2020)
Over the past few months, coronavirus disease 2019 (COVID-19) has assumed the character of a pandemic, leading to significant global mortality mostly because of COVID-19–related pneumonia. Pneumonia is likely to progress more severely in patients with underlying chronic lung disease. The purpose of this review is to discuss the management strategies in patients with chronic lung disease such as chronic obstructive pulmonary disease, asthma, pleural diseases, and obstructive sleep apnea during the COVID-19 pandemic, with current literatures and international guidelines.